(untitled) (Journal of Misan Researches, 2024)
The study aimed to shed light on the semiotics of the mind in the literary text, during revealing on thinking, perception, and activate the mind, logic and the structure of imagination at the level of creativity and narrative fiction, in opposed speech, speech, pronunciation, expression, applying to the letter of Ibn al-Amida to Ibn Balka, the study belongs to the descriptive study, with a semiotic analytical approach, the research included dealing in language semiotics and Convention and its concept in general and stages of development. The research also dealt in a brief summary about Ibn al-Amid as author and writer, and the reason for his addressing Ibn Balka with an analytical study of the letter. The study concluded that the semiotics of the mind nondependent in its study, but it is a link and interconnection of the semiotics of action, working and passions through which the mental event is formed, and the results also showed that (Ibn al-Amid) used the cognitive mental role, which was manifested in his speech, which enabled him to master this letter during sober language and style, (Ibn al-Amid) also used rhetorical methods that increased the rigidity of the situation, such as the method of ’antithesis, which gave him expressive power.